Whole body perfusion in patients undergoing frozen elephant trunk for type A acute aortic dissections. (March 2017) - Cappabianca, Giangiuseppe; Roscitano, Claudio; Bichi, Samuele; Cricco, Antonio; Parrinello, Matteo; Beghi, Cesare; Albano, Giovanni; Esposito, Giampiero
The Frozen Elephant Trunk (FET) can be adopted in selected type A acute aortic dissections (TAAAD). During FET, a prolonged distal circulatory arrest exposes the spine and visceral organs to potential ischemic injuries. Antegrade distal aortic perfusion (ADAP) could minimize this risk: we describe the technical aspects of the simultaneous use of antegrade cerebral perfusion (ACP) and ADAP achieving a "Whole Body Perfusion" (WBP) during FET.